Phytoremediation of Crude Oil Polluted Sandy Soil using Plant Leaves: A Comparative Study - Nnadikwe Johnson; Otaraku, Ipeghan Jonathan; Oji Akuma; Samuel Nwaozuzu (Journal Majelis Paspama, 2026)
This study evaluates the comparative efficacy of Jatropha curcas and Vernonia amygdalina leaf extracts in phytoremediating crude oil-polluted sandy soil. Leaf extracts containing P. aeruginosa, S. aureus, and E. coli were prepared via sun drying, room drying, and wet blending. Wet-blended extracts (10-40g, 40 days) achieved significant reductions: - Hydrocarbons: 2.40 μg/mL (Vernonia amygdalina), 2.11 μg/mL (Jatropha curcas). Lead (Pb): 0.99 μg/mL (Vernonia amygdalina), 0.72 μg/mL (Jatropha curcas). - Zinc (Zn): 0.71 μg/mL (Vernonia amygdalina), 0.51 μg/mL (Jatropha curcas). Predictive models (R² > 0.875) developed using Minitab software demonstrate the impact of leaf mass, treatment time, and soil pH on remediation. Results highlight the potential of these plant extracts as sustainable bio-remediation agents for crude oil-polluted sandy soil, offering an eco-friendly solution for environmental restoration.